A Stateful Approach to Generate Synthetic Events from Kernel Traces. (15th August 2012) - Ezzati-Jivan, Naser; Dagenais, Michel R.
Abstract : We propose a generic synthetic event generator from kernel trace events. The proposed method makes use of patterns of system states and environment-independent semantic events rather than platform-specific raw events. This method can be applied to different kernel and user level trace formats. We use a state model to store intermediate states and events. This stateful method supports partial trace abstraction and enables users to seek and navigate through the trace events and to abstract out the desired part. Since it uses the current and previous values of the system states and has more knowledge of the underlying system execution, it can generate a wide range of synthetic events. One of the obvious applications of this method is the identification of system faults and problems that will appear later in this paper. We will discuss the architecture of the method, its implementation, and the performance results.